Individual Development and Cultural Evolution of Arithmetical Thinking - Damerow, Peter
autorisierter Preprint; erscheint in: Strauss, S. (Ed.), Ontogeny and Historical Development. Norwood 1986. - KeiBi-relevant: p. 24-26: The Role of Early Civilizations in the Development of the Concept of Number; p. 26-37: The Origin of Numerical Notations in Mesopotamia